2021
DOI: 10.1038/s41598-021-97912-1
|View full text |Cite
|
Sign up to set email alerts
|

Method of estimating the effective zone induced by rapid impact compaction

Abstract: This paper proposes a method for estimating the effective zone, including effective depth and effective range of compaction degree, from rapid impact compaction (RIC) on sand layer whose fines content is less than 10%. The proposed method utilizes a string of microelectromechanical system accelerometers to monitor the acceleration at various depths and propagation distances during compaction. To interpret and extract useful information from monitored data, peak-over-threshold (POT) processing and normal distri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Previously published studies have reached the same conclusion for more coarse-grained soils. Although the compaction depth is assumed to depend slightly on both soil conditions (as discussed by Cheng et al, 2021) and compactor characteristics (e.g., dynamic reaction force), the results, together with previous studies, indicate that the plate size (side length) of the plate is a suitable parameter for estimating the compaction depth.…”
Section: Discussionmentioning
confidence: 63%
“…Previously published studies have reached the same conclusion for more coarse-grained soils. Although the compaction depth is assumed to depend slightly on both soil conditions (as discussed by Cheng et al, 2021) and compactor characteristics (e.g., dynamic reaction force), the results, together with previous studies, indicate that the plate size (side length) of the plate is a suitable parameter for estimating the compaction depth.…”
Section: Discussionmentioning
confidence: 63%
“…The literature reported that the hammer weight ranged from 50 to 120 kN and the drop height was about 1.2-1.5 m [1,5,6,8]. A higher drop height increased the compaction energy but also the compaction time.…”
Section: Rapid Impact Compaction Machinementioning
confidence: 99%
“…The existing ground level was lower than the expected apron level, so a fill embankment with a maximum height of 5 m from the surface was planned. The Rapid Impact Compaction (RIC) method was used to compact the fill embankment, as it can achieve an effective compaction depth of 3 to 5 m depending on the fine content of the soil [1,4,22]. To reduce the cost of fill material, two scenarios were tested: one using soil cut from the construction site with high fine content (SC), and the other using soil imported from outside with fine content lower than 20% (SM).…”
Section: Test Embankmentmentioning
confidence: 99%
See 1 more Smart Citation